PEMANFAATAN KARTU KONTROL SEBAGAI UPAYA PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS - Viny Lufiasari; Reni Dwi Setyaningsih; Tri Sumarni (Viva Medika, 2015)
Diabetes mellitus is a metabolic disease as the result of an abnormal insulin secretion, insulinworking, or both of them. World Health Organization said that were 347 million people in theworldwide have diabetes mellitus. Diabetes mellitus is incurable, but the blood sugar rate can controlled by four pillars management of diabetes mellitus they are education, diet, physical exercise,and pharmacological therapy. The Control card of diabetes mellitus can used as a reminder anddocumentation, and to facilitate in monitoring diabetes mellitus management. The purpose of thisresearch is to know the effect of utilization control card to the decrease of blood sugar rate on patientswith diabetes mellitus in Prodia Health Gymnastic Community of Purwokerto. The researchmethodology was used a Pre Experimental Method with Pre-Test and Post-Test One Group Design.The research result shows that the majority of respondents were in the age group 60-74 years (64%),and the most are women (64%) than man (36%) with an average experience of diabetes mellitus for <5 years (50%). The data indicated that control card has an effect on decrease of blood sugar rate onpatients with diabetes mellitus (p=0,018). Keywords: Control Card, Blood Sugar Rate, Diabetes Mellitus